2018
DOI: 10.1039/c8ob01108g
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium-catalyzed regioselective C8-H amination of quinolineN-oxides with trifluoroacetamide at room temperature

Abstract: A facile and efficient protocol for rhodium-catalyzed amination of quinoline N-oxides at the C-8 position using simple and commercially available trifluoroacetamide as the amino source has been developed, which proceeds with perfect regioselectivity at room temperature and short reaction times. This catalytic system is highly convenient on a gram scale. The desired products feature diverse functional group tolerance with good to excellent yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…This method overcomes the limitation of nitration [42] and annulation reactions [43] which were used to obtain biologically important C8-aminoquinolines, along with this the current method also has an advantage over previous methods that the starting material of amino source is commercially available (Scheme 18). [44] The authors have also depicted a tentative mechanism as shown in (Figure 8). [44] Firstly, the cationic species from dimeric rhodium catalyst [RhCp*Cl 2 ] 2 , was generated with the aid of a silver salt.…”
Section: Rh(iii)-catalyzed C(sp )à H Functionalization Of Quinolinesmentioning
confidence: 88%
See 2 more Smart Citations
“…This method overcomes the limitation of nitration [42] and annulation reactions [43] which were used to obtain biologically important C8-aminoquinolines, along with this the current method also has an advantage over previous methods that the starting material of amino source is commercially available (Scheme 18). [44] The authors have also depicted a tentative mechanism as shown in (Figure 8). [44] Firstly, the cationic species from dimeric rhodium catalyst [RhCp*Cl 2 ] 2 , was generated with the aid of a silver salt.…”
Section: Rh(iii)-catalyzed C(sp )à H Functionalization Of Quinolinesmentioning
confidence: 88%
“…[44] The authors have also depicted a tentative mechanism as shown in (Figure 8). [44] Firstly, the cationic species from dimeric rhodium catalyst [RhCp*Cl 2 ] 2 , was generated with the aid of a silver salt. In 2019, Sharma et al overcome the drawback of previous C-8 halogenation of quinoline which limited to iodination only [28] and disclose methodology for bromination in good to excellent yield.…”
Section: Rh(iii)-catalyzed C(sp )à H Functionalization Of Quinolinesmentioning
confidence: 88%
See 1 more Smart Citation
“…Loh and co‐workers also established an Rh III ‐catalyzed alternative strategy for the C8‐amidation of quinoline N ‐oxide using amidobenziodoxolone as the coupling partner . Very recently, Cui's group described another Rh III ‐catalyzed C8‐amidation of quinoline N ‐oxide using commercially available trifluoroacetamide . Recently, benzo[ c ]isoxazoles (anthranils) were highly successful as a bifunctional arylaminating agent under redox‐neutral conditions for the direct aryl amination of sp 2 and sp 3 C−H bonds and straightforward construction of N‐PAHs …”
Section: Figurementioning
confidence: 99%
“…[12] Very recently,C ui's group described another Rh III -catalyzed C8-amidation of quinoline N-oxide using commercially available trifluoroacetamide. [13] Recently,b enzo[c]isoxazoles (anthranils) were highly successful as ab ifunctional arylaminating agent under redox-neutral conditions for the direct aryl amination of sp 2 and sp 3 CÀHb onds [14,15] and straightforward construction of N-PAHs. [16][17][18][19] In ar ecent report, Hashmi andc o-workers studied Au III -catalyzed construction of 2-amino pyrroles and quinoline-based polyazaheterocycles( Scheme 1a).…”
mentioning
confidence: 99%